Fabrication and Characterization of Baobab Pod (Adansoniadigitata) FiberReinforced Polyester Resin Composite (Lafia Journal of Scientific and Industrial Research, 2024)
Baobab pod fibres were obtained from Sabo market in Zaria and sliced longitudinally, screened out from the baobab fruit, washed with water, dried under sun for fabrication and characterization. The fiber was extracted and treated with 5% NaOH solution. Important samples were fabricated with different fiber loading of 10wt%-30wt%. The samples were moulded using Hand Lay-up method followed by pressing and post cured at 60oC for 3 hours. The result showed tensile strength decreases as the loading of fiber increased from 20 wt% to 30 wt%. It was also observed that baobab composite has the highest tensile strength of 18.85 MPa at 20 wt% and least (16.45 MPa) at 15 wt%. The result also revealed the elongation at break increased from 20 wt% to 25 wt%. At 25wt% it has a maximum value (18.4%) elongation at break; at 30wt%. It was also observed that the density increased with increase in the fiber loading from 15wt% to 30wt% (1.23g/cm3 - 2g/cm3) respectively. At 15wt% shows a maximum water take-up of 6.53% while from 20 wt% to 30 wt%, Flexural strength increased from 10 wt% to 15 wt% (23.98MPa - 46.3Mpa). However, the bending stress decreases on increasing the fiber loading from 20-30 wt% (30.2 Mpa – 25.2 Mpa). The elastic nature of the composite generally increases with increased in fiber loading. This study, however recommend hybridization of baobab pod fiber with other natural fiber to investigate the mechanical and physical property of the hybrid composite for better result.